CF-RIP: a convergence-free mechanism for RIP protocol - WANG Bin1; ZHANG Jian-hui2; GUO Yun-fei2; LAN Ju-long2 (Tongxin xuebao)
In order to solve the problem of distance vector routing protocol converge very slowly to the correct routes when link costs increase,a new convergence-free routing protocol CF-RIP using RIP（routing information protocol） was proposed,which is based on failure-carrying packets and multiple viable next hops per destination.The new protocol eliminated the convergence period altogether and could solve the problem of count to infinity.The CF-RIP provided better stability and availability;meanwhile it was proved that a loop-free path to a destination if one such path exists.Simulations performed show that CF-RIP can dealing with the simultaneous failures of multiple arbitrary links effectively.